Integrating Socioscientific Issues into Worksheets: Enhancing Student Understanding of Chemical Kinetics - Sri Haryati; Erviyenni Erviyenni; Guspatni Guspatni; Tri Padila Rahmasari; Siti Nazhifah (STAI Hubbulwathan Duri, 2025)
Socioscientific Issues (SSIs) are real-world topics that integrate science content with societal relevance. This study aims to integrate SSIs into basic chemistry education—specifically chemical kinetics—by developing an Electronic Student Worksheet (E-LKM) that enhances conceptual understanding through contextualized issues. The E-LKM was developed using the 4D model: Define, Design, Develop, and Disseminate. The development process employed Flip Builder software to create an interactive, digital format that simulates an engaging e-book. Expert validation was conducted with two subject-matter experts through construct validation. Revisions were made based on detailed feedback. A small-scale trial was also conducted involving 13 students to assess usability and comprehensibility. Validation results indicated strong validity, with scores of 0.90 (content aspect) and 0.91 (media aspect). The trial revealed the need for clearer, more accessible language. Revisions included the integration of contextual news and simplified explanations to enhance student comprehension. The final version of the E-LKM successfully aligned with SSI syntax and pedagogical principles. The validated E-LKM effectively supports the teaching of chemical kinetics by engaging students with relevant, real-life issues. The integration of SSIs through interactive media fosters critical thinking and contextual learning. The findings confirm that the developed E-LKM can serve as an effective instructional tool in SSI-based chemistry education.